Nasal high flow therapy use in wards in patients with chronic obstructive pulmonary disease may spare ICU resources. (15th November 2021) - Trump, Matthew W.; Ganapathiraju, Iaswarya; Jackson, Julie A.; Branick, Kate; Taylor, Matt; Oetting, Trevor W.; Pelaez, Carol A.
Abstract: Nasal high flow therapy has been previously studied for the management of acute hypoxic respiratory failure in patients with chronic obstructive pulmonary disease but the data regarding its use outside of the intensive care unit are sparse. We aimed to evaluate safety and efficacy of nasal high flow therapy outside of the intensive care unit in patients with acute hypoxic respiratory failure and known chronic obstructive pulmonary disease. We conducted a retrospective matched historic cohort study of adult patients with diagnosed chronic obstructive pulmonary disease presenting with acute hypoxic respiratory failure between December 2017 to June 2019, after the initiation of a new protocol, which allowed patients to be managed with nasal high flow therapy on the medical/surgical wards instead of transferring them to the ICU per prior standard of care. Nasal high flow therapy was initiated either in the emergency department or on the medical/surgical wards. Patients were matched with historical cohorts who were managed with prior standard of care based on age, body mass index, comorbidities, and home oxygen use. Primary outcome of interest was difference in rates of mechanical ventilation. Secondary outcomes included hospital length of stay, total number of days spent in the intensive care unit, and in‐hospital mortality. A total of 90 patients met study inclusion criteria and were matched to 90 historical control patients. Among the study group, 8% required mechanical ventilation versus 9% in the control group ( p  = 0.79). Hospital length of stay was 7 days in study group versus 6 days in control group ( p  = 0.02), and in‐hospital mortality was the same in both study and control groups at 12% ( p  = 0.99). Nineteen percent of study group patients required ICU level of care at any time during the admission compared with 49% of control group ( p  < 0.001). Nasal high flow therapy use in patients with acute hypoxic respiratory failure and underlying chronic obstructive pulmonary disease outside of the intensive care unit may spare ICU resources and cost without delay in definitive care such as mechanical ventilation.